The future for the libraries: Information or communication - G. V. Gildebrant; Г. В. Гильдебрант (Scientific and Technical Libraries, 2020)
The findings of two sociological surveys held in Arkhangelsk in 2017-2018 are discussed: expert interviews “The thoughts on the future of libraries” and the poll “What are the libraries needed for?”. The administrators and experienced librarians, professors in library sciences and other specialists of the library sphere in several Russian regions took on the role of experts. The author summarizes their views on the current status of libraries, and suggests forecasts and recommendations for the future to all interested players: i.e. librarians, library administration, the ministry, and users. Over 500 Arkhangelsk residents participated in the online poll. The respondents are over 18 year-old age, and the survey appears to be representative in terms of gender and age. The topics under discussion are: frequency of visits to the library, relevancy of library services, user preferences. The Arkhangesk residents’ satisfaction with library services is evaluated; their attitude toward closing libraries is revealed, residents’ reviews are cited. Based on the survey findings, the collective portrait of opposite groups — frequent-goers and non-goers is described. The professional library community and the users contend that the libraries are highly demanded in the modern society. В статье освещены результаты двух социологических исследований, проведенных в Архангельске в 2017–2018 гг.: интервью экспертов «Размышления о будущем библиотечной сферы» и опроса «Для чего сегодня нужны библиотеки?». Среди экспертов – руководители и опытные специалисты библиотек, преподаватели библиотечных дисциплин и другие специалисты, вовлеченные в библиотечную сферу из нескольких регионов России. В статье представлено их обобщенное мнение о современном состоянии дел, даны прогнозы и рекомендации на будущее всем заинтересованным сторонам: библиотекарям, руководителям библиотек, министерству, пользователям. В онлайн-анкетировании приняли участие более 500 жителей Архангельска старше 18 лет, исследование репрезентативно по полу и возрасту ...